PERAN ASURANSI DALAM PENCAPAIAN SUSTAINABLE DEVELOPMENT GOALS (SGDS) - Ellectrananda Anugerah Ash-shidiqqi; Batari Laskarwati (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The insurance industry can be a driver of sustainable development by collecting premiums, but insurance has a problem, namely the public's low understanding of insurance, so it is necessary to educate the public about the role of insurance. insurance, sustainable development research results confirm that the importance of disaster insurance is an alternative priority in disaster management activities in Indonesia. Finally, insurance through sharia insurance can also play a role by targeting those who are not touched by conventional insurance for reasons of belief. With the largest Muslim population in the world at 222 million people, the possibility of groups that do not want to accept conventional insurance is very large, and this is where Islamic insurance can play a role. With the contribution of all sectors including insurance, hopefully Indonesia can become one of the countries with the highest progress in terms of achieving the SGD targets.